Power, Norms, and Trust: Interrelated Factors Impacting ASEAN Management of South China Sea Disputes - Serey, Rithiya (Muslim Politics Review, 2024)
In 1992, the Association of Southeast Asian Nations (ASEAN) officially recognized and called for a peaceful resolution to the South China Sea disputes. It has now been more than 30 years since it did so, but ASEAN has not resolved the disputes, resulting in economic and security problems in the region. This paper explores ASEAN’s ineffectiveness by showing the interrelationship between otherwise siloed sets of explanatory factors, such as material interests and the practice of ASEAN norms. In addition, it highlights the importance of the dynamics of trust, a rarely examined and understudied element in ASEAN diplomacy, based on documentary analysis and interviews with regional experts and officials. The paper offers a detailed empirical account of ASEAN diplomacy, and contributes to international relations literature more generally by theorizing the interrelationship between dependency, trust, and the practice of diplomatic norms. Most importantly, it provides the operationalization and application of the concept of trust in the South China Sea disputes, for the first time, to explain ASEAN's ineffectiveness. It demonstrates that social trust is an essential component of the background knowledge that constitutes ASEAN diplomats’ reflexive behaviors and practices toward conflict resolution.